Providing Prenatal Care in a Student Run Free Clinic - Chloe Warpinski; Nathan Burke; Sanaz Dovell; Michelle McCraw; Caroline King; Amy Stanley; Krystal Stennett; Tory Finley; Michelle Nall; Mallory LeBlanc; Nicole Diaz; Phillip Mackie; et al. (Journal of Student-Run Clinics, 2024)
Background: Prenatal care is a cornerstone of maternal and child health. This paper describes the creation of a free prenatal clinic for uninsured families following recognition of a significant disparity in birth outcomes in Alachua County, Florida including: the development of essential community re- source collaborations, clinical operations in a dual aim patient care-medical education site, preliminary outcomes after one year of clinical operation, identified challenges, and next steps for our growing program.Methods: A retrospective chart review of all sixteen patients enrolled with the student run free prenatal clinic in its first year of clinical operation. Analysis included assessment of the prenatal care course using descriptive statistics. Specific dimensions assessed include timing of transition of care to a traditional obstetrics clinic, clinical findings and diagnoses identified at the prenatal clinic, and birth out- comes during the study period and report findings as descriptive statistics.Results: The clinic has demonstrated the ability to identify and treat numerous pathologies which may impact maternal-fetal morbidity and mortality. The clinic has seen very high rates of patient retention and has demonstrated successful transition of patients to higher levels of care when indicated. Finally, the clinical model provides an uncommon opportunity for medical and physician assistant students to care for patients throughout the first 32 weeks of pregnancy and receive additional training in point-of-care ultrasound, diagnostics, and medical decision making.Conclusion: While the small sample size limits the ability to assess the effectiveness of the prenatal clinic intervention, there are numerous promising features based on preliminary results.